Typology of traditional courtyard houses as muslim functional spaces in low rise residential units, Iraq - Haraty, Hayder Jawad Shakir (2015)
A courtyard is an important transitional functional space with unique aesthetic design element used for Islamic social and cultural activities in traditional Iraq’s residential units and contributes to the Islamic identity of Iraq. However,their utilization is currently diminishing in Iraq’s new residential development due to lack of understanding of its Islamic function. There is a need to analyze the manner the existing Iraq’s traditional courtyards function as Islamic spaces and be integrated into the new residential development in Iraq. This study investigates how the traditional courtyards houses in Iraq embraces and enhances the relevant Islamic principles in relation to the overall residential unit layout and their potentials to be applied in the Iraqi new low rise residential units. Physical observations on the physical design characteristics and morphological studies on the form and planning on eight traditional Iraq’s courtyards houses were conducted. Subsequently, photographical and morphological analysis were utilized in interpreting the data. The study concludes that the traditional courtyards do posses certain Islamic principles in the planning and design which were either spontaneously implemented or as initially intended by the residents. This is due to the fact that compliance to Islamic principles was not made compulsory by local building authority. This study significantly fills the gap in the design of new Islamic residential courtyard houses worldwide to integrate both the Islamic principles and lifestyles in more meaningful manners.